Digital Pressure Meter Equipped with Temperature and Humidity - Abdul Cholid; Her Gumiwang Ariswati; Syaifudin Syaifudin (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2020)
Calibration is a technical activity which consists of the determination, the determination of one or more properties or characteristics of a product, process or service in accordance with a special procedure has been set. The purpose of which is to ensure the calibration measurement results in accordance with national and international standards. The tools used for the calibration of pressure Digital Pressure Meter. This tool is used to measure the pressure and suction pump spygnomanometer or other devices that use parameters for measuring pressure. This module manufacturing system using Arduino system as a controller and as processing analog data into digital data of the sensor MPX5100GP and MPXV4115V using analog signal conditioning circuit and displayed on the LCD Touchscreen with 2 modes of measurement that is positive pressure and vacuum pressure with pressures ranging from 0-300 mmHg for positive pressure and 0 –(-400) mmHg to vacuum pressure. There are also DHT22 sensor, As a detector for temperature and humidity for use in the work method in the calibration process. Based on a stress test generated and using comparators Digital Pressure Meter 2 plus brand fluke, this tool has an error value of 0 to 0.58% and has a value increment or correction value of 0 - 3. It can be concluded that the DPM DUA MODE this deserves to be used.